2012
DOI: 10.1164/rccm.201107-1293oc
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Attenuates Hypoxic Pulmonary Hypertension via Estrogen Receptor–mediated Effects

Abstract: E2 attenuates hemodynamic and remodeling parameters in HPH in an ER-dependent manner, through direct antiproliferative mechanisms on vascular cells, which may provide novel nonhormonal therapeutic targets for HPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
188
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 147 publications
(205 citation statements)
references
References 76 publications
11
188
1
5
Order By: Relevance
“…The data from this study strongly support the notion that the rescue action of E 2 is mainly mediated through ER-b in MCT-induced PH [22]. LAHM et al [23] reported that a non-selective ER inhibitor and ER-a-and ER-b-specific antagonists opposed the effects of E 2 ; however, they considered that the important effects of E 2 on functional end-points in hypoxic PH were predominantly mediated by ER-a. Therefore, evaluation of ER expression in PH was considered important.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The data from this study strongly support the notion that the rescue action of E 2 is mainly mediated through ER-b in MCT-induced PH [22]. LAHM et al [23] reported that a non-selective ER inhibitor and ER-a-and ER-b-specific antagonists opposed the effects of E 2 ; however, they considered that the important effects of E 2 on functional end-points in hypoxic PH were predominantly mediated by ER-a. Therefore, evaluation of ER expression in PH was considered important.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, evaluation of ER expression in PH was considered important. The data of LAHM et al [23] indicate that hypoxia increased ER-b, but not ER-a, lung vascular expression. In contrast, our results showed that MCT inhibited ER-a, but had no effect on ER-b proteins in the lung.…”
Section: Discussionmentioning
confidence: 92%
“…This hypothesis was explored in a study by LAHM et al [74] which demonstrated that E2 attenuates the decline in haemodynamic and remodelling parameters observed in hypoxia-induced PH in rats. In this model, the benefits of E2 are mediated by the oestrogen receptor and conversion to E2 metabolites is not required [74]. However, a protective role for E2 in human PAH has yet to be demonstrated.…”
Section: Oestrogen Signallingmentioning
confidence: 99%
“…As such, this pathway may be another potential therapeutic target. Despite evidence to support the benefits of E2 in rat hypoxia-induced PH [74], the strong female predominance in human PAH makes E2 less appealing as a potential therapy as there are concerns that E2 may promote PAH in humans. Instead, targeting the pathways downstream of E2, e.g.…”
Section: Oestrogen Signallingmentioning
confidence: 99%
“…Oestrogen effects are therefore highly context and compartment specific. For example, E2 has been shown to stimulate pulmonary artery smooth muscle cell proliferation but to exert anti-proliferative effects in pulmonary artery endothelial cells [6][7][8]31]. Similarly, in a recent microarray analysis of lungs from chronically hypoxic rats treated with E2, the E2-regulated genome indicated that E2 regulates multiple genes whose activation or inhibition is consistent with anti-proliferative effects, but that E2 also induces changes consistent with pro-proliferative or pro-angiogenic effects [32].…”
mentioning
confidence: 99%